Analisis Penerapan Deret Ukur dalam Perhitungan Laju Pertumbuhan Penduduk Terhadap Tingkat Kemiskinan - Syahnaz Salsabila; Ade Sri Agustin; Shinta Kirana Wijayanti; Dedek Kustiawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to analyze the application of a series of measures in calculating the rate of population growth to the poverty rate. The measuring series in the economy is a model of population growth. Population growth is a change in the number of inhabitants in a population that occurs over a certain period. Judging from data from BPS (Central Statistics Agency) regarding the population growth rate in 2015-2022, there are similar differences. BPS also stated that Indonesia's population growth rate in 2020-2025 was 0.9%. In research conducted using the literature study method which is one type of qualitative research which uses references derived from books, scientific articles such as journals, proceedings that are in accordance with the topic to be discussed. The purpose of applying the measuring series in the calculation of the population growth rate to the poverty rate is to predict the number of inhabitants in 2023-2025 and its effect on the poverty rate. An increasing population will result in a large gap between the population, low quality and ability of the population, causing an increase in the level of poverty.